HUBUNGAN METODE JOB ORDER COST DENGAN PENENTUAN HARGA POKOK PRODUKSI PADA PT. AGRONESIA INKABA - Hanny Mulyawati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
ABSTRACT : Title autor submitted in research is “relationship method Job Order Cost with determination cost of good manufacture PT. AGRONESIA Inkaba “rubber engineering industry division” Research methods used is assosiatif to from interactive relationships interaktif with data collection : study documentation, observasion, interview and the study of literature and with the data processing technicues by using the accounting calsulation (Normative Base Price and the Cost of Variable ) and Statistical Calculation Product Moment Correlation and Analysis Technique using tables Interpretation .based on the result of research in the field obtained accounting calculation result is the total value of variable x (cost of normatif ) amount Rp.18.985.57 and the total value of variable Y (cost of variable) amount Rp.29.614.73. from that result calculating statistic (product moment corelation ) so obtained amount 0,99. based on the calculated, the authors concluded that hypothesis that the authors propose it proved. where job order cost method has a very strong relationship and significant to determining the cost of good manufactured at PT.Agronesia inkaba rubber and enggineering industrial division.